2016
DOI: 10.1093/toxsci/kfw067
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Safety Profile of a Depleting Antibody against CRTh2 for Asthma: Well Tolerated Despite Unexpected CRTh2 Expression on Vascular Pericytes in the Central Nervous System and Gastric Mucosa

Abstract: CRTh2 is expressed on immune cells that drive asthma pathophysiology. Current treatment options for severe asthma are inadequate and therapeutic antibody-mediated depletion of CRTh2-expressing cells represents a promising new therapeutic strategy. Here we report for the first time that CRTh2 is not only expressed on immune cells, but also on microvasculature in the central nervous system (CNS) and gastric mucosa in humans. Microvascular expression of CRTh2 raises a safety concern because a therapeutic antiCRTh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In this report, we developed an automated high-throughput platform to perform on-tip affinity capture using MSIA D.A.R.T.’S tips (Thermo Fisher Scientific), with rapid digestion and peptide elution into a 96-well plate followed by LC–MS analysis. We applied the automated platform to study the levels of in vivo deamidated anti-CRTh2, a therapeutic antibody candidate targeting CRTh2 ( C hemoattractant R eceptor-homologous molecule expressed on Th2 cells). , CRTh2 is expressed on human immune cells such as eosinophils, basophils, type-2 innate lymphoid cells, and Th2 cells that mediate allergic inflammation and asthma pathogenesis. Anti-CRTh2 has been shown in mouse models of Th2 inflammation to deplete CRTh2-expressing immune cells that are important in allergy and asthma, , thus has the potential to be a novel therapeutic for the management of allergic inflammatory diseases such as asthma.…”
mentioning
confidence: 99%
“…In this report, we developed an automated high-throughput platform to perform on-tip affinity capture using MSIA D.A.R.T.’S tips (Thermo Fisher Scientific), with rapid digestion and peptide elution into a 96-well plate followed by LC–MS analysis. We applied the automated platform to study the levels of in vivo deamidated anti-CRTh2, a therapeutic antibody candidate targeting CRTh2 ( C hemoattractant R eceptor-homologous molecule expressed on Th2 cells). , CRTh2 is expressed on human immune cells such as eosinophils, basophils, type-2 innate lymphoid cells, and Th2 cells that mediate allergic inflammation and asthma pathogenesis. Anti-CRTh2 has been shown in mouse models of Th2 inflammation to deplete CRTh2-expressing immune cells that are important in allergy and asthma, , thus has the potential to be a novel therapeutic for the management of allergic inflammatory diseases such as asthma.…”
mentioning
confidence: 99%
“…One of them is a DP2-targeting antibody, which could deplete inflammatory cells, including eosinophils, ILC2, and T H 2 cells, and therefore may present a novel therapy for asthma (Huang et al, 2016b). Preclinical studies indicated a low risk of central nervous system or gastrointestinal toxicity associated with this antibody (Rajapaksa et al, 2016).…”
Section: B New Opportunities In G Protein-coupled Receptor Drug Devementioning
confidence: 99%